Enhancing the solubility and foam ability of rice glutelin by heat treatment at pH12: Insight into protein structure. (June 2020) - Zhao, Meng; Xiong, Wenfei; Chen, Boxuan; Zhu, Jie; Wang, Lifeng
Abstract: Glutelin in the rice protein content of up to 80% (dry basis), due to its alkali-soluble protein, severely limited the application of rice protein, a high-quality hypoallergenic plant protein, as an ingredient in the food industry. Herein, rice glutelin dissolved in alkaline solution (pH12) was heat treated for 30 and 60 min at different temperatures (60, 80, 100 °C). It was found that the solubility of glutelin at pH7 after heating at 100 °C for 60 min increased by about 3 times compared with native protein, as well as foaming ability increased by about 2 times and exhibited good foam stability. Dynamic light scattering (DLS) and atomic force microscopy (AFM) results showed that the heat treatment (100 °C, 60 min) resulted in a decrease in the size (about 100 nm) of globular glutelin aggregates, accompanied by a reduction in disulfide bond content and an increase in surface net potential and hydrophobicity. Sodium dodecyl sulfate–polyacrylamide gel (SDS–PAGE) electrophoresis, UV–visible, intrinsic fluorescence and infrared spectroscopy characterization revealed that the primary, tertiary and secondary conformations of glutelin were altered due to heat treatment. In addition, small angle X-ray scattering (SAXS) results suggested that the glutelin aggregates were more flexible after heat treatment. These dimensional and structural changes contributed to the improvement of rice glutelin functional properties after heat treatment, implying that this combination of alkali and heat treatment has potential for enhancing the performance of rice proteins. Graphical abstract: Image 1 Highlights: Solubility and foaming ability of glutelin increased by 3 and 2 times after heating 60 min at 100 °C. Disulfide bond of glutelin was destroyed after heating (100 °C, 60 min) as well as conformations changes. The rice glutelin aggregate size was reduced by about 100 nm after heat treatment (100 °C, 60 min). The structural flexibility of rice glutelin was enhanced after heat treatment (100 °C, 60 min) at pH12.